Odpowiedzi

2009-10-07T12:46:35+02:00


a) y =x2 +x
W(-1)= (-1)2+(-1) = 1-1 = 0 W(-1) =0 , to -1 jest pierwiastkiem równania
W(2)= (2)2+ (2) = 4+2 = 6 W(2)nie jest równe 0, to 2 nie jest pierwiastkiem równania
W(1)= (1)2+ (1) = 1+1 = 62 W(1)nie jest równe 0, to 1 nie jest pierwiastkiem równania

b)y=2x2 + 2x + 4
W(-1)= 2(-1)2+2(-1) +4= 2-2+4 = 4 W(-1)nie jest równe 0 , to -1 nie jest pierwiastkiem równania
W(2)= 2(2)2+2 (2)+4 = 8+4+4 = 16 W(2)nie jest równe 0, to 2 nie jest pierwiastkiem równania
W(1)= 2(1)2+ 2(1)+4 = 2+2+4 = 8 W(1)nie jest równe 0, to 1 nie jest pierwiastkiem równania


c)y=(2x+2)( x-1) = 2x2 – 2x + 2x – 2 = 2x2-2
W(-1)= 2(-1)2 - 2 = 2-2 = 0 W(-1) =0 , to -1 jest pierwiastkiem równania
W(2)= 2(2)2-2 = 8-2 = 6 W(2)nie jest równe 0, to 2 nie jest pierwiastkiem równania
W(1)= 2(1)2-2 = 2-2 = 0 W(1)= 0, to 1 jest pierwiastkiem równania